A HOPEFUL NOTE IN VASIL STEFANIK’S WORKS AND WAYS OF ITS CREATION - Babych, N. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
This article strives to identify and to explain the place and content of bright notes (arch. nuty) in Vasyl Stefanyk’s novellas and prose poems voiced in the score of physical, material and moral pain that their characters, and together with them the author himself, the symbol of life and death, through and who was pursued by the rose – suffered.